Contemporary needs of animation programmes in business tourism - Bosanac, Katarina; Ivančić, Ivana; Dragičević, Daniel (Oeconomica Jadertina, 2026)
Tourism is most often viewed as a human need arising from the modern way of life, characterized by a specific need for activity, participation, and engagement. Business events and tourism are different but closely related services that a destination offers to visitors who seek a different experience during their stay. Every tourist destination and facility must diversify its service offerings by relying on various attractions, where animation holds great potential for expanding the offer, especially in terms of diversity. Animation, as a type of activity, explains its attractiveness through innovative content, diversity of technological approaches, and the broad possibilities of using and implementing animation in various spheres of socio-cultural activities. Accordingly, animation programs as part of the business tourism offering are an important element in meeting the needs of the modern guest, as they represent an aspect that can provide more than expected. Delighting participants after or outside of business activities is a challenge that offers an opportunity for significant growth and development among competing events. Participants expect nothing less than an unforgettable experience, which creates additional pressure on organizers to find ways to add value to the event experience. The constant pursuit of differentiation is key to capturing guests' attention and ensuring the success of the event and this is precisely the research problem. Which trends in animation programmes are best suited to the needs of modern business event users. The research was conducted through interviews with six respondents directly involved in the organization of business events. The research was conducted during February and March 2023. The results showed that, alongside leading trends in technology and sustainability, innovation and creativity stand out the most. Therefore, digital solutions at live events, combined with well-designed sustainable and socially-oriented animation programs, have the potential to become an integral part of the business industry. The contribution of this work is reflected in the analysis of trends in animation programs at business events and in defining specific trends that will characterize the offerings of animation programs in business tourism in the coming period.
Keywords: animation programs; business tourism; trends; technology; sustainability